2019
DOI: 10.4312/as.25.2.37-51
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to Retirement: Perceptions of Portuguese Older Men

Abstract: In this paper we present results based on the project Old Guys Say Yes to Community. We interviewed 90 men in southern Portugal between 60 and 93 years of age. Our main aim was to understand how older men experienced their transitions from work to retirement. We clarify the concept of transition and the models that explain transitions in the life course perspective. There are a number of factors to consider during the processes of retirement. Also, not much is known about the role of education and learning dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, the living conditions of the countries in question must be considered. Although it is one of the lowest in Europe, the cost of living in Portugal is higher than in Brazil (Numbeo, 2019), meaning the reported income may not be sufficient to meet the retiree's basic needs, as is the case with Brazilian retirees (Almeida et al, 2015;Guerson et al, 2018;Valadas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the living conditions of the countries in question must be considered. Although it is one of the lowest in Europe, the cost of living in Portugal is higher than in Brazil (Numbeo, 2019), meaning the reported income may not be sufficient to meet the retiree's basic needs, as is the case with Brazilian retirees (Almeida et al, 2015;Guerson et al, 2018;Valadas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate the findings of other studies of retirement that show the need for retirees to continue working part-time to survive in both countries. In Portugal, Valadas et al (2019) emphasized that most retirees have low capital due to a lifetime of low wages and limited ability to save for retirement, so that the only way to maintain their health and socialization is to continue working. Similarly, in Brazil, Guerson et al (2018) found that satisfaction with their income was one of the principal determinants of satisfaction with life for retirees who continue working after retirement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the classes take place in the evenings so that people who work in daytime can join them as well (City of Espoo, 2019a). Valadas, Vilhena, and Fragoso (2019) studied Portuguese men at the transition stage to retirement and found out that education and learning have an immense impact on the lives of older adults. Education had shaped the life paths of men, but it also affected directly and indirectly their motivation and ability to continue learning in later life.…”
Section: What Is the Role Of Adult Learners?mentioning
confidence: 99%